Survey of Non-Cash Food Aid Users in East Banjarmasin District - Singgih Priono; Septeria Noor Yuliannisa; Bakhtiar; Muhammad Jamili; Ali Khamdan (Jurnal PubBis, 2022)
Non-cash Food Aid Users (BPNT) is food aid from the government that is given to Beneficiary Families (KPM) every month through an electronic account mechanism which is used only to buy food at E-Warong (Electronic Mutual Cooperation Stalls). In Presidential Regulation Number 63 of 2017 that the Indonesian people who get BPNT are people who are classified as poor even though in its implementation there are many things that do not match the amount of assistance with the basic needs of the community so that this assistance is complained of by the community. This research, entitled "Satisfaction Survey of Non-Cash Food Assistance Users in East Banjarmasin District", has a formulation of the problem of how satisfied BPNT program users are in East Banjarmasin District. The purpose of this study was to determine the user satisfaction of the BPNT program in East Banjarmasin District. This research uses descriptive quantitative method using several data collection techniques such as questionnaires, observation, and documentation. The data sources used are primary data from questionnaires and observations and secondary data from the regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform of the Republic of Indonesia Number 14 of 2017. Data will be analyzed using a Likert scale and community satisfaction index. Based on the results of the research that has been carried out, the community satisfaction survey consists of 9 indicators, then there are indicators that must be improved, namely time indicators, officer competence and complaints handling indicators, while the indicators that are maintained are requirements indicators, procedures, product specifications, costs, behavior. officers and infrastructure, based on the calculation of SKM, the results obtained are 75.875 compared to table II between 65.00 - 76.60 with interval C values converted to quality Service Unit performance is in a poor position.